(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Volkivska D. A. Scientific approaches to understanding the potential of the individual. The article deals with the essence of the concept of «individual capacity» and presents the results of theoretical analysis research potential of the individual scientists from different fields.